Dampak Penambahan Campuran Aspal Penetrasi 60/70 Sebanyak 3% pada 1 Lapisan dan 3 Lapisan Struktur Balas - Dian Setiawan M; Bobby Ariyanto (Civil Engineering Department, Universitas Muhammadiyah Yogyakarta, 2022)
The addition of asphalt material is expected to increase service life and minimize maintenance costs from conventional ballast structures. The purpose of this study was to determine the weight of test material + asphalt 3%, compressive strength, vertical deformation, elastic modulus, abrasion value and damage to the test specimen after loading. The method used was the compressive test method while for the test object used consists of dirty ballast, clean ballast, dirty ballast + 3% asph alt 1 layer, dirty ballast + 3% asphalt 3 layers, clean ballast + 3% asphalt 1 layer, clean ballast + 3% asphalt 3 layers. The test objects were modeled with a cube measuring 0.4 x 0.3 x 0.2 m. The test results show that the addition of asphalt can increase the deformation value and can reduce the modulus of elasticity. However the presence of asphalt as a binding material can minimize the valueof abrasion and damage to the reciprocating constituent material.Â